QUALITY CONTROL STUDIES AND DETERMINATION OF TOTAL FLAVONOID AND PHENOLIC CONTENT OF AN AYURVEDIC SOLID DOSAGE FORM - GAYATRI S; ANGEL SESLIN MONICA V; CHITRA K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Ayurvedic preparations contain a mixture of herbs. Blood glucose regulator (BGR)-34 is an Ayurvedic tablet meant for the treatment of diabetes. The objective of the present work is to carry out the quality control (QC) studies of BGR-34 tablets. Materials and Methods: QC tests for the tablet were carried out such as determination of average weight, pH value, tablet hardness, friability, and disintegration time as per official method. Determination of natural antioxidants such as total flavonoid and total phenolic content was also carried out by standard methods. Standardization of ayurvedic preparation involves the determination of marker compound. Gallic acid content was determined using high-performance liquid chromatography. Results: The results indicated that the tablet passes the QC tests. The tablet was found to have 32.31±0.91 mg quercetin equivalents/100 g of total flavonoid content and 2.285±0.12 mg gallic acid equivalents (GAE)/100 g of phenolic content. The amount of gallic acid present in the sample was found to be 2.06%. Conclusion: The presence of large amounts of flavonoids may be the reason for its hypoglycemic activity. The present study can be used for the regular QC of the BGR-34 tablets.